2001
DOI: 10.1017/s1355838201000218
|View full text |Cite
|
Sign up to set email alerts
|

The intramolecular stem-loop structure of U6 snRNA can functionally replace the U6atac snRNA stem-loop

Abstract: The U6 spliceosomal snRNA forms an intramolecular stem-loop structure during spliceosome assembly that is required for splicing and is proposed to be at or near the catalytic center of the spliceosome. U6atac snRNA, the analog of U6 snRNA used in the U12-dependent splicing of the minor class of spliceosomal introns, contains a similar stem-loop whose structure but not sequence is conserved between humans and plants. To determine if the U6 and U6atac stem-loops are functionally analogous, the stem-loops from hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 29 publications
2
18
0
Order By: Relevance
“…The lack of stable U6-AGC base pairing to the U6-ISL in T. vaginalis might indicate folding instability of this structure. Nevertheless, our model supports the importance of the upper portion of this stem (McPheeters 1996;Shukla and Padgett 2001) as well as the formation of the U6 ISL pentaloop GNR(N)A, similar to that proposed in other organisms (Huppler et al 2002). Structure-function analyses of the T. vaginalis spliceosomal proteins and snRNAs will be necessary to test whether these structural differences impact splicing mechanisms in this divergent eukaryote.…”
Section: Discussionsupporting
confidence: 84%
“…The lack of stable U6-AGC base pairing to the U6-ISL in T. vaginalis might indicate folding instability of this structure. Nevertheless, our model supports the importance of the upper portion of this stem (McPheeters 1996;Shukla and Padgett 2001) as well as the formation of the U6 ISL pentaloop GNR(N)A, similar to that proposed in other organisms (Huppler et al 2002). Structure-function analyses of the T. vaginalis spliceosomal proteins and snRNAs will be necessary to test whether these structural differences impact splicing mechanisms in this divergent eukaryote.…”
Section: Discussionsupporting
confidence: 84%
“…Some of this overlap is likely to be due to the presence of the U5 snRNP in both tri-snRNP complexes. In addition to the protein similarities, we have shown that an important RNA element of U6 snRNA can functionally replace the analogous element of U6atac snRNA (Shukla and Padgett 2001). More recently, we have also shown that U4atac snRNA can be functionally replaced by U4 snRNA providing that it can base pair with U6atac snRNA (Shukla and Padgett 2004).…”
Section: Introductionmentioning
confidence: 82%
“…Comparison of U6 and U6atac snRNAs showed that the central regions were either highly conserved or interchangeable based on our previous studies (Shukla and Padgett 2001). We therefore focused on the 59 and 39 ends of the RNAs, which are quite different (see Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, it could be shown that the intramolecular stem-loop structure of U6 snRNA can indeed functionally replace the U6atac snRNA stem-loop (32). Despite the fact that the U4/U6 and U4atac/U6atac snRNA duplexes exhibit analogous secondary structures, the overall sequence similarity between the corresponding snRNAs is not very high (approximately 40% between both U6 and U6atac and U4 and U4atac snRNAs) (35).…”
Section: Discussionmentioning
confidence: 99%